Shalat fardu berjamaah dan perannya dalam membentuk kepemimpinan siswa - Ilyasa, Ridhwan Akmal; Supriadi, Dedi; Muhlisin, Sofian (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The implementation and education of congregational fardu prayers for the formation of student leadership is a crucial aspect in character cultivation. This research emerged based on an understanding of the benefits of congregational fardu prayers and their implementation on leadership development in the school environment. This study was compiled to find out the implementation of congregational fardu prayers for students, find out the attitude of student leadership, and identify the influence of congregational fardu prayers on the formation of leadership of grade VIII students at MTs Ibnu Taymiyah Bogor. This study uses a quantitative approach with a survey causal associative research method. The population consisted of 103 students and the sample consisted of 82 students with simple random sampling. The data collection technique of this study uses questionnaires and documentation. The data analysis technique uses descriptive data testing and inferential data with the Pearson product moment correlation formula, to determine the correlation between congregational obligatory prayers and leadership formation. Based on the analysis, the implementation of congregational fardu prayers was categorized as medium with a percentage of 52.4% of students, the low category with a percentage of 24.4% of students, and the high category with a percentage of 23.2% of students. The formation of leadership shows that it is categorized as medium with a percentage of 59.8% of students, a low category with a percentage of 24.0%, and a high category with a percentage of 18.3%. Based on the analysis of the product correlation test, the moment shows a calculation of 0.895 > a table of 0.220 or a significance value of 0.000 < 0.05 with the interpretation of the data classified as 0.81-0.99, which means that there is a very strong relationship between variable X and variable Y. The results achieved indicate that there is a significant influence on the higher the implementation of congregational fardu prayers, the higher the formation of student leadership. Abstrak Pelaksanaan dan pendidikan salat fardu berjamaah terhadap pembentukan kepemimpinan siswa merupakan aspek krusial dalam penanaman karakter. Penelitian ini muncul berdasarkan pemahaman kemanfaatan salat fardu berjamaah dan implementasinya terhadap pengembangan kepemimpinan di lingkungan sekolah. Penelitian ini disusun untuk mengetahui pelaksanaan salat fardu berjamaah siswa, mengetahui sikap kepemimpinan siswa, dan mengidentifikasi adanya pengaruh salat fardu berjamaah terhadap pembentukan kepemimpinan siswa kelas VIII Di MTs Ibnu Taimiyah Bogor. penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian survei asosiatif kausal. Adapun populasi terdiri dari 103 siswa dan sampel terdiri dari 82 siswa dengan pengambilan simple random sampling. Teknik pengumpulan data penelitian ini menggunakan kuesioner dan dokumentasi. Teknik analisis data menggunakan pengujian data deskriptif dan data inferensial dengan rumus korelasi pearson product moment, untuk mengetahui korelasi antara salat fardu berjamaah dan pembentukan kepemimpinan. Berdasarkan analisis bahwa pelaksanaan salat fardu berjamaah terkategori sedang dengan persentase 52,4% siswa, kategori rendah dengan persentase 24,4% siswa, dan kategori tinggi dengan persentase 23,2% siswa. Adapun pembentukan kepemimpinan menunjukkan bahwa terkategori sedang yaitu dengan persentase 59,8% siswa, kategori rendah dengan persentase 24,0%, dan kategori tinggi dengan persentase 18,3%. Berdasarkan analisis uji korelasi product momen menunjukkan rhitung 0,895 > rtabel 0,220 atau nilai signifikansi 0,000 < 0,05 dengan interpretasi data tergolong pada angka 0,81-0,99 berarti adanya hubungan sangat kuat antara variabel X terhadap variabel Y. koefisien determinasi menunjukkan pada angka sebesar 80,10%. Hasil yang dicapai tersebut mengindikasikan adanya pengaruh signifikan semakin tinggi pelaksanaan salat fardu berjamaah maka semakin tinggi pembentukan kepemimpinan siswa.